2020
DOI: 10.1021/acsami.9b17694
|View full text |Cite
|
Sign up to set email alerts
|

Additive Preparation of Conductive Circuit Based on Template Transfer Process Using a Reusable Photoresist

Abstract: To solve the problems of a conventional subtractive process for preparing conductive circuits, numerous alternative additive processes have been investigated, such as screen or inkjet printing, selective electroless plating, laser-induced forward transfer, etc. They all lead to a simpler procedure, less pollution, and finer line width but are still faced with difficulties like low conductivity and thickness, poor adhesion, and high cost. PDMS is a kind of material with low surface energy, leading to low adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In the past decades, the selective metallization technology has attracted enormous attention due to its wide applications in communication equipment, electronic devices, medical appliance, energy storage devices, , light-emitting displays (LED), and wearable devices . At present, the commonly used metallization methods include photolithography, ink printing, micro-contact printing, screen printing, and laser-induced selective metallization (LISM). LISM is the technology that uses lasers to activate the polymer surface and then conducts electroless plating to deposit the metal layer on the activated area.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, the selective metallization technology has attracted enormous attention due to its wide applications in communication equipment, electronic devices, medical appliance, energy storage devices, , light-emitting displays (LED), and wearable devices . At present, the commonly used metallization methods include photolithography, ink printing, micro-contact printing, screen printing, and laser-induced selective metallization (LISM). LISM is the technology that uses lasers to activate the polymer surface and then conducts electroless plating to deposit the metal layer on the activated area.…”
Section: Introductionmentioning
confidence: 99%
“…Templated electrodeposition is a fast, high‐throughput, and high‐resolution technique, and has been successfully deployed in the fabrication of micromesh transparent electrode, [ 47 ] disordered nanowire electronics, [ 48 ] and conductive circuits on flexible substrates. [ 49 ] Hence, the introduction of templated electrodeposition in plasmonic metasurfaces fabrication may lead to a new avenue for high‐efficiency and cost‐effective production of plasmonic metasurfaces. However, few studies have been reported templated electrodeposition in plasmonic metasurfaces, thus it still needs intensive investigation to be successfully employed.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of selective metallization, photolithography can prepare large-area high-precision metal patterns, but it requires masks and clean rooms, increasing production costs. The ink printing method is relatively simple and economical, while fabricating a conductive pattern based on ink printing requires printing and subsequent sintering, including thermal sintering, electric sintering, microwave sintering, flash lamps, and laser sintering . All these methods possess both merits and drawbacks.…”
Section: Introductionmentioning
confidence: 99%